Increasing accuracy of measuring thermal conductivity of liquids by using the direct heating thermistor method - Matvienko, Sergey; Vysloukh, Sergey; Martynchyk, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2016)
The work is devoted to the research of thermal and physical characteristics of different materials by the nondestructive method. We propose to determine thermal conductivity of liquids by using the method of thermistor direct heating. Essential disadvantage of many existing methods for determining thermal and physical characteristics (TPC) is the use of the methods of destructive control of materials and products, which significantly complicates measuring and makes it impossible to simultaneously measure a large number of experimental samples, as well as does not allow obtaining the required accuracy of measurement results. So there exists a task of developing a device, which has high accuracy and can simultaneously measure a large number of thermal and physical characteristics of the studied samples, thereby increasing the efficiency of measurements. We designed a device for measuring thermal conductivity of liquids, the principle of work of which is based on the method of thermistor direct heating. The results of experimental studies using reference liquids are presented, obtained with the help of the developed device. They demonstrated high accuracy and efficiency of its use in determining thermal conductivity of liquids. The result is achieved by introduction of additional coefficients of proportionality to the calculation formulas for determining thermal conductivity of the studied liquids, which are determined by testing the thermistors with the use of reference liquids with known TPC. The conducted studies revealed that the value of measurement error per one session of 10 minutes by different probes amounted to not higher than 2 %, while in the course of measuring the same studied fluid by 60 probes simultaneously the error did not exceed 1.5 %. Using the proposed method of thermistor direct heating, due to the small size of the probe and simple design of the device, allows applying it in various sectors of industry, medicine and biology to determine TPC of different materials with high accuracy of measurements.